2019
DOI: 10.1051/0004-6361/201935024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ionization feedback on star formation: a case study of the M 16 H II region

Abstract: Aims. We aim to investigate the impact of the ionized radiation from the M16 H II region on the surrounding molecular cloud and on its hosted star formation. Methods. To present comprehensive multi-wavelength observations towards the M16 H II region, we used new CO data and existing infrared, optical, and submillimeter data. The 12 CO J=1-0, 13 CO J=1-0, and C 18 O J=1-0 data were obtained with the Purple Mountain Observatory (PMO) 13.7m radio telescope. To trace massive clumps and extract young stellar object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 89 publications
2
13
0
Order By: Relevance
“…Some observations have shown that several components can be observed toward bright rimmed clouds (BRCs) due to the internal dynamics caused by the interaction, although the presence of an IBL and/or 8 µm is often taken as proof of an interaction with the ionizing flux. Statistical studies using Spitzer, ATLASGAL, and Herschel showed that H II bubbles host at least 25−30% of the high-mass Galactic sources (Deharveng et al 2010;Kendrew et al 2012Kendrew et al , 2016Palmeirim et al 2017) and dedicated studies show the same behavior (Tigé et al 2017;Russeil et al 2019;Xu et al 2019). Therefore, this high percentage of young high-mass sources was mainly thought to be the result of different triggering mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Some observations have shown that several components can be observed toward bright rimmed clouds (BRCs) due to the internal dynamics caused by the interaction, although the presence of an IBL and/or 8 µm is often taken as proof of an interaction with the ionizing flux. Statistical studies using Spitzer, ATLASGAL, and Herschel showed that H II bubbles host at least 25−30% of the high-mass Galactic sources (Deharveng et al 2010;Kendrew et al 2012Kendrew et al , 2016Palmeirim et al 2017) and dedicated studies show the same behavior (Tigé et al 2017;Russeil et al 2019;Xu et al 2019). Therefore, this high percentage of young high-mass sources was mainly thought to be the result of different triggering mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Individual feedback modes have been assessed for large samples of sources (e.g., Rosero et al 2019), and measurements of the relative role of multiple feedback modes have been done for particular starforming regions (e.g. Lopez et al 2011;Pellegrini et al 2011;Ginsburg et al 2017;Lee et al 2019;Xu et al 2019) and across many regions (e.g. Lopez et al 2014;Chevance et al 2019;Kruijssen et al 2019;McLeod et al 2019; Barnes et al 2020;McLeod et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, Eden et al (2013) found that most of the molecular clouds associated with H II regions have CFE as high as 40%. The clump formation efficiency obtained in the M16 H II region is 22±3% (Xu et al 2019). Figueira et al (2020) estimated that the CFE of H II region RCW 120 varies between 12 and 26%.…”
Section: Properties and Formation Of Cores In Afgl 333-ridgementioning
confidence: 97%